Answer:
g(3a – 6) = a - 4
Step-by-step explanation:
g(x) = 1/3x - 2
g(3a – 6) = 1/3(3a – 6) - 2
= a - 2 - 2
= a - 4
Answer:
Step-by-step explanation:
g(x) = -2f(x)
Vertical stretch by virtue of the factor 2
Reflection over the x-axis by virtue of the factor -1
First let us find the length of JN
JN =JK +KN
JN = 82+105 = 187
JN=187..............(1)
UC= JN -( JH +HU+CN)
We are given :
JH= 22, HU = 96 and CN = 51
plugging all the values we get
UC = 187-( 22+96+51)
UC =187 -169
UC = 18
Answer is UC =18 ( option B)
Answer:
3 sips equal a gulp
Step-by-step explanation:
we have
----> equation A
Divide by 2 both sides
----> equation B
equate equation A and equation B
Group terms that contain the same variable
therefore
3 sips equal a gulp
I hope this helps you
1/4+3/7
7/7.4+3.4/7.4
7/28+12/28
19/28